The Effect of Olive Oil (Extra Virgine Olive Oil) and Moderate-Intensity Exercise On The Level of High Density Lipoprotein (HDL) in Male Wistar Strain Rat (Rattus novergicus L) Which Was Given High Fatty Diet - Anwari, Ikhsan Syakban; Sutysna, Hendra (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: Dyslipidemia is a condition where there is an abnormal lipid profile in the blood. Modern patterns and lifestyles such as consuming fast food cause excessive fat consumption which can increase the possibility of contracting blood vessel and heart disease. High levels of High Density Lipoprotein (HDL) cholesterol can protect the body against heart disease and stroke, but not many drugs can increase HDL cholesterol levels. Olive oil is an oil that contains 77% Mono Unsaturated Fatty Acid (MUFA) which can reduce LDL cholesterol and increase HDL cholesterol. Objective: To determine the effect of olive oil (Extra Virgine Olive Oil-EVOO) and moderate intensity exercise on high density lipoprotein (HDL) levels in male Wistar strain (Rattus novergicus L) rats fed a high-fat diet. Method: a true experimental research design with a pretest and posttest design with a control group (Pretest and Posttest with Control Group) with simple randomization. Results: There was an increase in HDL levels in the control group (42.50 to 44.50 mg / dl), the olive oil treatment group was (50.83 to 53.33) mg / dL, the moderate intensity exercise treatment group (46.67 to 52 , 00 mg / dl), and the moderate-intensity exercise and olive oil treatment groups (47.50 to 58.67 mg / dl). Conclusion: Extra Virgine Olive Oil, moderate intensity exercise, and Extra Virgine Olive Oil with moderate intensity exercise influence the increase of HDL levels in the blood of male Wistar strain rats fed a high-fatty diet.